A novel method for improving the printability of cement-based materials: Controlling the releasing of capsules containing chemical admixtures. (April 2022) - Shao, Lijing; Feng, Pan; Zuo, Wenqiang; Wang, Haochuan; Geng, Zifan; Liu, Qi; Miao, Changwen; Liu, Zhaolong
Abstract: As an emerging additive manufacturing technology in construction, 3D printed concrete (3DPC), has different requirements on rheological properties of cement-based materials in the fresh state. On the one hand, low yield stress or so-called high flowability of printed materials must be delivered by the pump system and extruded swimmingly. On the other hand, high yield stress guarantees the shape of printed materials upon deposition. Therefore, the rheological properties of fresh materials demand a mutation in a short time before and after extrusion from the nozzle. In this paper, a novel method controlling the release of accelerators and thickeners from responsive capsules by external stimulations was introduced and used in 3DPC to adjust the rheological properties of printed materials. This study first focuses on the preparation and characterization of the "smart" capsules. Secondly, the practicality of this method on controlling the rheological properties of cement-based materials was investigated. Our results show that, the printed materials were able to keep high flowability before extrusion. After applying the stimulations, the flowability decrease dramatically accompanied by the increase in yield stress, which improves the buildability of printed materials. This proposed method provides a novel approach to actively tune the rheology of 3DPC and with this new method, pastes with high flowability are qualified to be printed, which further broadens the mix design of the cement-based materials for printing.